The location of the cause of dormancy, viability and seed decay in the silver fir Abies alba Mill. - Nada Gogala; M. Vardjan (Acta Biologica Slovenica)
The seed coat was shown to be the major site of the cause of dormancy in the seed of fir Abies alba, partially also the embryo, particularly the radicle. This part of the embryo dies first during stor age. It seems that the radicle is that part of the seed which is the least resistant and the least viable.